2022
DOI: 10.1002/ptr.7595
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin regulates T cell differentiation by promoting αVβ8 expression in bone marrow‐derived dendritic cells to alleviate inflammatory bowel disease

Abstract: Inflammatory bowel disease is a disease that can invade the whole digestive tract and is accompanied by immune abnormalities. Immune dysfunction involving dendritic cells (DCs) and T cells is recognized as a key factor in diseases. Indirubin (IDRB) exerts antiinflammatory effects and can help in treating immune diseases. This study aimed to isolate bone marrow‐derived dendritic cells (BMDCs) using lipopolysaccharide (LPS) to obtain mature DCs (mDCs). The expression of CD80, CD86, CD40, and MHC‐II was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This deficiency in integrin αvβ8 has been associated with the induction of colitis [ 31 ]. In line with this, Zhang et al [ 32 ] reported that indirubin induces dendritic cell activation and apoptosis by upregulating αvβ8 expression. This induction not only facilitates antigen uptake but also inhibits antigen presentation and T-cell activation.…”
Section: Preclinical Evidence and Mechanisms Of Actionmentioning
confidence: 68%
See 1 more Smart Citation
“…This deficiency in integrin αvβ8 has been associated with the induction of colitis [ 31 ]. In line with this, Zhang et al [ 32 ] reported that indirubin induces dendritic cell activation and apoptosis by upregulating αvβ8 expression. This induction not only facilitates antigen uptake but also inhibits antigen presentation and T-cell activation.…”
Section: Preclinical Evidence and Mechanisms Of Actionmentioning
confidence: 68%
“…An increase in the Th17/Treg ratio was reported in DSS-induced IBD mice, and IN regulated this imbalance. In the study by Zhang et al [ 32 ], the administration of indirubin to DSS-induced mice increased Foxp3 and IL-10 expression, accompanied by a decrease in RORγt and IL-17 expression. Gao et al [ 27 ] further supported these findings by demonstrating elevated levels of Foxp3 and IL-10 following the single or combined administration of indirubin and isatin .…”
Section: Preclinical Evidence and Mechanisms Of Actionmentioning
confidence: 99%